PEMAHAMAN EMPAT PILAR KEBANGSAAN DALAM MENGHADAPI ARUS GLOBALISASI DI SMA NEGERI 1 CARENANG, KABUPATEN SERANG, PROVINSI BANTEN - Yohanes Oci; Zakaria Habib Al-Ra’zie; Ratu Yasmin Adara Dinanti; Ade Nur Komalasari (Tensile : Jurnal Pengabdian Kepada Masyarakat, 2024)
Indonesia is a country formed from approximately 17,000 islands spread from Sabang to Merauke. Apart from that, the country consists of various tribes, religions, races and customs and is rich in regional languages ​​so that it is all united within the framework of the Unitary State of the Republic of Indonesia. This is a basis for consideration so that all citizens understand the need for unity and integrity and the need to implement the values ​​of Pancasila and it is deemed necessary to practice the motto Bhinneka Tunggal Ika in everyday life as a glue for national unity and integrity. In this era of modernization, the influence of foreign cultures has a huge impact on the nation's next generation, however, this development not only causes negative aspects, but there are also positive things that must be adopted to increase the creativity of the nation's children for economic progress and development of the nation and state. Before carrying out this Community Service (PKM) activity, the PKM team prepared several important agendas to carry out this activity effectively and efficiently, such as: 1) The chairman and team members held regular meetings to discuss the Community Service (PKM) theme, 2) Conducting a survey at SMA Negeri 1 Carenang, Serang City, Banten Province and obtaining permits and determining the time for carrying out activities, the theme of this PKM is Socialization of the Four Pillars of Nationality, where the target is for all students to provide an understanding of the values ​​of Pancasila, the 1945 Constitution as a constitution, the Republic of Indonesia as a home of pluralism, and Bhinneka Tunggal Ika as a motto to maintain the unity and integrity of the nation and state. To overcome this problem, a method was used to provide students with an understanding of the importance of implementing the values ​​of Pancasila and Bhinneka Tunggal Ika in everyday life. Keywords: Four Pillars of Nationality and Globalization.